Implementation of Propemperda Policy in the Bukittinggi City DPRD Environment - Edward, Aurelia Valentin; Frinaldi, Aldri (Adabi : Journal of Public Administration and Business, 2023)
Propemperda as a planning document that can be used to measure the achievement of the performance of the establishment of Local Regulations. Propemperda is implemented by the DPRD and Local Government based on the regional policy. Propemperda Bukittinggi city 2019 realized 8 out of 22 draft regional regulations. At least Propemperda Bukittinggi city realized, it is necessary to look at the implementation of Propemperda policy in the DPRD bukittinggi city. The theory of implementation according to Van Meter and Van Horn there are 6 (six) variables that affect: Standards and Purposed of Policy, Resources, Characteristics of Implementing Organizations, Interorganization Communication, Disposition, and Social, Economic, and Political Factors. This research uses a descriptive qualitative research method with the inductive approach. The data collection techniques are obtained from observations, interviews, and documentation. The collected data is analyzed with data reduction techniques, data display, and concluding. The results of the data analysis that Propemperda is not realized because proposals outside Propemperda are more important. In addition, human resources are also limited due to different educational backgrounds, as well as a lack of experts. The DPRD Bukittinggi city also lacks socialization of Propemperda to related parties. Finally, it was suggested to the DPRD Bukittinggi to be equipped comprehensively about Propemperda through technical guidance, and more actively conduct Propemperda socialization.